2023
DOI: 10.3390/life13081679
|View full text |Cite
|
Sign up to set email alerts
|

Soccer, Sleep, Repeat: Effects of Training Characteristics on Sleep Quantity and Sleep Architecture

Abstract: Due to the high demands of competitive sports, the sleep architecture of adolescent athletes may be influenced by their regular training. To date, there is no clear evidence on how training characteristics (intensity, time of day, number of sessions) influence sleep quality and quantity. 53 male soccer players (M = 14.36 years, SD = 0.55) of Austrian U15 (n = 45) and U16 elite teams (n = 8) were tested on at least three consecutive days following their habitual training schedules. Participants completed daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Relative maximum power, relative average power, and heart rate were recorded during each type of exercise, fingertip blood was collected at the immediate end of exercise for blood lactate concentration analysis using an EKF portable blood lactate meter (EKF Lacate-Scout, EKF, Germany) and subjects were asked about their level of fatigue by Borg (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Rating of Perceived Exertion (RPE) scale.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative maximum power, relative average power, and heart rate were recorded during each type of exercise, fingertip blood was collected at the immediate end of exercise for blood lactate concentration analysis using an EKF portable blood lactate meter (EKF Lacate-Scout, EKF, Germany) and subjects were asked about their level of fatigue by Borg (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Rating of Perceived Exertion (RPE) scale.…”
Section: Designmentioning
confidence: 99%
“…Studies have found that prolonged high-intensity training and excessive sports competition may disrupt the athletes' circadian rhythm, making it difficult for them to fall asleep at night and causing daytime fatigue ( 14 16 ). Especially on the night before a competition, athletes may face emotions such as tension and excitement, increasing the risk of insomnia ( 17 19 ). Additionally, athletes may be affected in their ability to fall asleep and sleep quality due to issues such as bodily pain and muscle soreness during the training process, consequently affecting their training and competitive performance ( 18 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise alone may not effectively increase participants' anaerobic capacity, which is also crucial for football. Therefore, problems may arise if the exercise programme does not include appropriate anaerobic exercises (Frytz et al, 2023). Innovations in aerobic training to increase VO2max in amateur football athletes can achieve better and more efficient results by combining interval training with movements similar to football games, such as short sprints or sudden accelerations.…”
Section: Introductionmentioning
confidence: 99%